Sintering properties and development of ternary ZnAl2O3 phase in Al2O3 - ZnO composite ceramics - Sriyananda, I.B.P.B.; Thanihaichelvan, M. (University of Jaffna, 2021)
Zinc doped aluminium oxide (ZnAl2O3) is a wide bandgap semiconducting material with optical transparency. The wideband gap of 3.6 eV makes it as an interesting material in several applications like gas and chemical sensors and photovoltaic devices [1]. In this work, we studied the sintering properties of the alumina (Al2O3) and zinc oxide (ZnO) composite ceramics. The Al2O3 based ceramic matrix nanocomposite reinforced by 5 mol.%, 10 mol.%, 15 mol.% of zinc oxide (ZnO) nanoparticles, has been prepared and consolidated by pressureless sintering method. Nearly fully dense composite could be obtained by sintering at 900°C for 2 h. X-ray diffraction (XRD) has been used to characterize the as-prepared and sintered powders. X-ray diffraction results revealed that the samples were crystalline with a hexagonal wurtzite phase. As the concentration of alumina (Al2O3) increases in ZnO, the X-ray diffraction peaks shifts towards higher angle. This shifting in peak position and decrease in intensity reﬂect that Al is successfully replaced Al in ZnO matrix and the formation of ZnAl2O3. Previous studies have reported the formation of the ternary ZnAl2O3 phase at sintering temperature 1200°C and above. However, the phase development was observed at relatively lower temperature of 900°C in this study. Further studies could pave the way to the fabrication of ZnAl2O3 composite at low cost for several applications.
Keywords: Alumina; Zinc oxide; XRD; Sintering